The role of psychological flexibility in the relationship between empathy and flourishing among clinical nurses: a cross-sectional mediation analysis - Xiangjun Guo; Li Liu; Hangqin Lv; Meichuan Lin; Liping Chen; Hanting Zhang; Menghan Liu; Yutong Liu; Wenyan Jiang; Xiaoyun Liu (Frontiers in Psychology, 2026)
Background Clinical empathy is essential for high-quality patient care; however, its association with nurses' positive psychological functioning remains insufficiently understood. Psychological flexibility may be relevant to this association because it reflects how nurses respond to the difficult internal experiences that may arise during emotionally demanding care. This study examined the cross-sectional associations among clinical empathy, psychological flexibility, and flourishing in clinical nurses and evaluated the indirect association through psychological flexibility. Methods A cross-sectional study was conducted among 545 clinical nurses recruited from three tertiary Grade A hospitals in Sichuan Province, China, in May 2026. Self-reported data were collected on clinical empathy, psychological flexibility, flourishing, and sociodemographic and work-related characteristics. Pearson correlation analysis, hierarchical multiple linear regression, and statistical mediation analysis using the SPSS PROCESS macro (Model 4) were conducted. The indirect association was evaluated using 5,000 bootstrap resamples with percentile bootstrap confidence intervals. Results The mean flourishing score was 46.13 (SD = 8.21). Flourishing was positively correlated with empathy ( r = 0.157, p < 0.001) and psychological flexibility ( r = 0.662, p < 0.001), whereas empathy was weakly correlated with psychological flexibility ( r = 0.129, p = 0.002). In the final regression model, psychological flexibility showed a strong positive association with flourishing (β = 0.627, p < 0.001), whereas the adjusted direct association between empathy and flourishing was small (β = 0.066, p = 0.034). The estimated indirect association through psychological flexibility was 0.046 (BootSE = 0.016, 95% percentile bootstrap CI [0.013, 0.078]). In sensitivity analyses, the indirect association remained statistically significant across different covariate specifications, although its magnitude was attenuated after concurrently measured job satisfaction was included. Conclusions Psychological flexibility was more strongly and consistently associated with flourishing than empathy. The significant indirect association through psychological flexibility was consistent with the hypothesized model but does not establish temporal or causal mediation because all variables were measured concurrently. Longitudinal and intervention studies are needed to clarify the temporal ordering of these constructs and to determine whether changes in psychological flexibility precede changes in flourishing.